(untitled) (Research, Society and Development, 2023)
Introduction: Hypovitaminosis D and Metabolic Syndrome (MS) are conditions that have a high epidemiological prevalence and several risk factors in common. Although the mechanisms involved in this association are not very well understood, vitamin D deficiency has been suggested as an etiological factor in the development of insulin resistance, which is the main factor involved in the pathophysiology of MS. Objective: to investigate whether there is effectiveness of vitamin D supplementation in the remission of Metabolic Syndrome. Material and Methods: systematic review of randomized and cohort clinical trials, published between 2016 and 2021, in PuBmed, Lilacs/Medline, according to PRISMA recommendations. The GRADE system was applied to assess the quality and scientific evidence. Inclusion criteria, according to the PICOD question (Population; Intervention; Comparator; Output/result; Study design): adolescents and adults with metabolic syndrome, both sexes, using Vitamin D supplementation; studies with control group and metabolic syndrome remission outcome. Results: of the 713 articles identified, only 4 were analyzed, according to the mentioned criteria. Of these, only 1 showed remission of MS, due to vitamin D supplementation, due to the decrease in systolic and/or diastolic blood pressure, glycemic levels and triglyceride concentration. Conclusion: the results found in this study are still contradictory and do not allow us to affirm the effectiveness of vitamin D supplementation in the remission of the metabolic syndrome and that other factors, such as age and lifestyle, can be decisive in the action of vitamin D.